2010
DOI: 10.1111/j.1752-7325.2010.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for oral health literacy in an urban dental clinic

Abstract: Objective Studies show that the average person fails to understand and use health care related materials to their full potential. The goal of this study was to evaluate a health literacy instrument based on the Rapid Estimate of Adult Literacy in Medicine (REALM) that incorporates dental and medical terms into one 84-item Rapid Estimate of Adult Literacy in Medicine and Dentistry (REALM-D) measure and determine its association with patient characteristics of a culturally diverse dental clinic population. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
114
1
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(138 citation statements)
references
References 19 publications
16
114
1
7
Order By: Relevance
“…We classified education as a predisposing factor because of its strong association with health literacy (12,13), which in turn predicts higher sealant prevalence (10). This classification is also consistent with Andersen and Aday’s identification of education as a predisposing factor in their PEN model (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified education as a predisposing factor because of its strong association with health literacy (12,13), which in turn predicts higher sealant prevalence (10). This classification is also consistent with Andersen and Aday’s identification of education as a predisposing factor in their PEN model (17).…”
Section: Discussionmentioning
confidence: 99%
“…The RAND Health Insurance Experiment (HIE) also found that health literacy (ie, parents’ knowledge of the medical care system) predicted use of dental health services among children (11). Studies further suggest that one of the strongest predictors of medical and oral health literacy is educational attainment (12,13). Knowledge of the preventive benefits of sealants is also almost 5 times higher among people with more than a high school education compared with those without a high school education (34% vs 7%) (14).…”
Section: Introductionmentioning
confidence: 99%
“…Low health literacy is often described as ‘The Silent Health Epidemic’ in which there is a limited capacity to obtain, comprehend and act on health information (2). The same definition used in oral context is called ‘Oral Health Literacy (OHL)’.…”
Section: Introductionmentioning
confidence: 99%
“…In the limited oral health research that has been done on this topic, similar results have been found (Lee, Divaris, Baker, Rozier, Vann, 2012). The body of work on self-efficacy and health literacy has generally used three well-tested scales for measuring health literacy: the Newest Vital Sign (Weiss, Mays, Martz, Castro, DeWalt, Pignone et al, 2005), the Rabid Estimate of Adult Literacy in Medicine (REALM) (Davis, Long, Jackson, Mayeaux, George, Murphy et al 1993) or Dentistry (REALD) (Atchison, Gironda, Messadi, & Der-Martirosian, 2010; Stucky, Lee, Lee, Rozier, 2011), and the Test of Functional Health Literacy in Adults (TOFHLA) (Baker, Williams, Parker, Gazmararian, & Nurss, 1999; Parker, Baker, Williams & Nurss, 1995). While each study revealed significant findings, no study used more than one health literacy measure to note any differences across the sample depending on measure used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other, shorter versions of the REALM have been attempted, but with limited application (Bass, Wilson, & Griffith, 2003; Arozullah et al, 2007). Versions of REALM have been created for oral health literacy, such as REALD-30, REALD-99, and REALMD (Atchison et al, 2010; Stucky et al, 2011). These measures model the original REALM in that they are lists of terms related to dental and oral health care that are to be read aloud by the participant.…”
Section: Literature Reviewmentioning
confidence: 99%